Phenotypic and morphometric characterization of Janwal Pashmi dog - MAKNE, S K; NANDEDKAR, P V; THAKUR, R R; CHOPADE, M M; ALI, S SAJID; DIGE, M S (The Indian Journal of Animal Sciences, 2024)
Janwal Pashmi is the medium sized dog found in the villages of Chakur tehsil of Latur and adjoining districts of Marathwada region of Maharashtra. Present investigation was carried out by collecting morphometric data on 207 Janwal Pashmi dogs from its breeding tract. Data collected was classified into two age groups, i.e. below one year (puppies) and above one year (adult). Majority of the dogs were found to be black in colour (78.26%), however, fawn (8.69%), brown (4.34%), grey (5.79%) and white (2.89%) were also noticed. Most of the dogs were found to have medium hairs length (51.20%) followed by long hairs (43.47%) and rarely short hair length (5.31%). The head was straight and wedge shaped with 69.56% and 30.43%, respectively. The colour of nostrils in majority of dogs was black (95.16%) and very few dogs had brown (3.86%) and pinkish (0.96%) colour nostrils. Eyes were light brown (47.34%) to dark brown (52.65%). Majority of dogs had long ear (54.58%) while medium sized ears were observed in 42.02% of dogs. Morphometric characters studied were body weight (BW), height at wither (HW), body length (BL), chest girth (CG), paunch girth (PG), tail length (TL), head length (HL), height at base of tail (HBT), neck length (NL), neck girth (NG), ear length (EL), ear width (EW), eye width (EYW), hind foot length (HFL), upper hind leg length (UHLL), lower hind leg length (LHLL), fore foot length (FFL), upper fore leg length (UFLL) and lower fore leg length (LFLL). The effect of sex was found to be non-significant on all the traits in puppies except BW, HW, HBT, NL, UHLL and UFLL. However, BW, HW, BL, CG, TL, HL, HBT, NL, NG, HFL, UHLL, LHLL, FFL and UFLL were found significantly higher in males of adult age group. Both vegetarian and non-vegetarian food was given to dogs and majority of farmers used iron mesh cages for keeping dogs. The characterization of Janwal Pashmi dog done in this study may help in the registration of this dog as a breed status and further conservation.